Greening the campus of a Brazilian university: cultural challenges - Marques Pereira, Giovana da Silveira; Jabbour, Charbel [UNESP]; Borges de Oliveira, Sonia V. W.; Teixeira, Adriano Alves [UNESP] (Emerald Group Publishing Limited, 2014)
Purpose - This study examined the relationship between environmental management practices developed at a campus of a Brazilian university (University of Sao Paulo) and the greening of its organizational culture. The paper aims to discuss these issues.Design/methodology/approach - This article presents a theoretical background based on the concepts of environmental management, organizational culture and environmental management in higher education institutions. The main framework of this research is the model proposed by Harris and Crane.Findings - The studied university has an environmental management program that is sometimes constrained in the following ways: the university bureaucracy and hierarchy; the main performance indicators for lecturers and professors are based on scientific production and publication, giving them little time for complementary activities; and some units develop their own environmental management practices, but they are not disseminated as best practices for use by other units. Some academic units showcase the proactive actions of professors who incorporate environmental management into their daily activities. The general perception is that the phrase environmental management is almost synonymous with solid waste management.Originality/value - This research details the first Brazilian application of the Harris and Crane model. It contributes an original analysis of environmental management and green organizational culture of a Brazilian university, an organizational type that has seldom been studied to date.
Keywords: Higher education; Sustainability; Brazil; Organizational culture; Environmental management